2019
DOI: 10.3390/polym11071191
|View full text |Cite
|
Sign up to set email alerts
|

Curing of Epoxy Resin DER-331 by Hexakis(4-acetamidophenoxy)cyclotriphosphazene and Properties of the Prepared Composition

Abstract: The method of optical wedge revealed that the optimum temperature for compatibility of hexakis(4-acetamidophenoxy)cyclotriphosphazene (ACP) and DER-331 epoxy resin is in the range of 220–260 °C. The interdiffusion time of components at these temperatures is about 30 min. The TGA and differential scanning calorimetry (DSC) methods revealed the curing temperature of 280 °С for this composition. IR spectroscopy confirmed that the reaction between the resin and ACP is completed within 10 min. According to the DSC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…The process of the Oswald ripening is also possible. Similar effects were observed earlier on oligomeric systems in [40,41].…”
Section: Particles Dissolution Kinetics Of Dispersed Phasessupporting
confidence: 89%
“…The process of the Oswald ripening is also possible. Similar effects were observed earlier on oligomeric systems in [40,41].…”
Section: Particles Dissolution Kinetics Of Dispersed Phasessupporting
confidence: 89%
“…Previously, we have shown that parameters of the critical point of a phase diagram (PD) and its distance from the curing isotherm determine the type of the forming phase structure and sizes of the phases [ 14 , 15 ]. Thus, the properties of heterogeneous systems are dependent on the mutual solubility and translational mobility of the components and kinetics of the chemical reaction, which affect the formation of the phase structure of the composite material and their properties [ 8 , 9 , 10 , 11 , 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The other example is hexaphenoxycyclotriphosphazene, which is used as a highly effective flame retardant for a large number of synthetic polymers. A number of effective flame-retarded functional epoxy resins, amine curing agents and benzoxazines with a phosphazene core have been proposed [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Carboxyl-containing epoxyphosphazenes and their use as a catalyst for the polymerization of benzoxazines have also been reported [ 22 ].…”
Section: Introductionmentioning
confidence: 99%